2014
DOI: 10.3746/jkfn.2014.43.5.705
|View full text |Cite
|
Sign up to set email alerts
|

Hypopigmenting Effects of Extracts from Bulbs of Lilium Oriental Hybrid 'Siberia' in Murine B16/F10 Melanoma Cells

Abstract: In order to develop a skin-whitening agent, melanin contents and intracellular tyrosinase activity were determined by western blotting. Ethyl acetate fractions of 80% ethanol extracts from lily (Lilium Oriental Hybrid 'Siberia') bulbs (R-EA) inhibited melanin synthesis in a dose-dependent manner in α-melanocyte stimulating hormone (α-MSH)-treated B16/F10 murine melanoma cells. Intracellular tyrosinase activity and melanin contents were suppressed by 45% and 74%, respectively, in response to treatment with 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, excessive generation of melanin pigments can lead to hyperpigmentation-related diseases, such as malignant melanomas [ 3 ]. Tyrosinase, the main enzyme in the melanin biosynthesis pathway, promotes the hydroxylation of L-tyrosine to L-DOPA (L-3,4-dihydroxyphenylalanine), and then promotes the oxidation of L-DOPA to dopachrome and dopaquinone, which synthesizes melanin through the auto-oxidation process by tyrosinase-related proteins (TRP-1 and 2) through several stages [ 4 , 5 , 6 ]. To date, methods of inhibiting melanin formation by impeding tyrosinase-related proteins have been widely used in the cosmetics industry for the development of skin-whitening agents [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive generation of melanin pigments can lead to hyperpigmentation-related diseases, such as malignant melanomas [ 3 ]. Tyrosinase, the main enzyme in the melanin biosynthesis pathway, promotes the hydroxylation of L-tyrosine to L-DOPA (L-3,4-dihydroxyphenylalanine), and then promotes the oxidation of L-DOPA to dopachrome and dopaquinone, which synthesizes melanin through the auto-oxidation process by tyrosinase-related proteins (TRP-1 and 2) through several stages [ 4 , 5 , 6 ]. To date, methods of inhibiting melanin formation by impeding tyrosinase-related proteins have been widely used in the cosmetics industry for the development of skin-whitening agents [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hydroquinone and arbutin work as competitive inhibitors, C 2 -ceramide and tretionin inhibit through blocking transcription, and linoleic acid and α-linolenic acid act by degrading tyrosinase ( 2 ). Additionally, the extracts of several plants and algae have been reported to suppress α-melanocyte stimulating hormone (MSH)-stimulated melanogenesis through sustained ERK 1/2 activation ( 3 – 6 ). There have been several investigations on anti-melanogenesis of methylated compounds, such as diosgenin, α-tocopheryl ferulic acid, and 2,5-dimethyl-4-hydroxy-3(2 H )-furanone ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional Korean medicine, lilies have long been used to treat lily disease, a mentally debilitating condition, as the root has the ability to stop coughing and stabilize the mind, and it is especially known to be effective in treating chronic obstructive pulmonary disease, the main symptoms of which are dry cough and shortness of breath [6][7][8]. Studies have also been reported on the whitening effect of lily root and its active ingredients [9].…”
Section: Introductionmentioning
confidence: 99%